A toolkit for parental engagement: from project to process. (15th March 2018) - Goodall, Janet
ABSTRACT: This article reports on and analyses a yearlong project supporting school staff to increase parental engagement with children's learning. Working with 34 schools, the project included the provision of a toolkit (information and activities) as well as opportunities for school to school learning. The project was useful for all schools, but some schools experienced profound changes in outlook, belief and practices. The major influences of change in this project were professional discussion, the use of the tools provided and reflection on both tools and discussion. The article concludes with a discussion of the implications for school leaders.